PENGARUH MOTIVASI KERJA DAN LINGKUNGAN KERJA TERHADAP KINERJA KARYAWAN PADA PT. KENLEE INDONESIA DIVISI PRODUKSI DI PARUNG BOGOR - Riska Purnaliasari; Rino Dedi Aringga (Yayasan Sahabat Cendekia Jaya, 2024)
Purpose. The purpose of this study was to determine the effect of work motivation and work environment on employee performance at PT. Kenlee Indonesia Production Division in Parung Bogor. The method used is quantitative approach, with a population of 400 employees. Metode. The sampling technique used the Slovin technique with an error level of 10%, thus obtaining a sample of 80 respondents. Data analysis using validity test, reliability test, classical assumption test, regression analysis, correlation coefficient, coefficient of determination and hypothesis testing. Results. The results of this study are work motivation has a significant effect on employee performance with a determination coefficient value of 57.4% and hypothesis testing obtained t count > t table or (10.252 > 1.991). Implications. The work environment has a significant effect on employee performance with a coefficient of determination of 67.9% and the hypothesis test is obtained t count > t table or (8.169 > 1.991). Work motivation and work environment simultaneously have a significant effect on employee performance with the regression equation Y = 6.694 + 0.512X1 + 0.324X2. The coefficient of determination is 64.5% while the remaining 35.5% is influenced by other factors. Hypothesis testing obtained F count > F table or (70.032 > 2.720).